Pengembangan Aplikasi Pencatatan dan Pengingat Tablet Tambah Darah Berbasis WhatsApp untuk Remaja Putri - Arifin Ilham; Maula Ismail Mohammad; Lina Khasanah; Bambang Karmanto; Suratmi Suratmi (Politeknik Negeri Jember, 2026)
Iron deficiency anemia among adolescent girls remains a major public health issue in Indonesia, partly due to low adherence to Iron and Folic Acid Supplementation (IFAS) tablet consumption and the lack of an individual-based monitoring system. This study aimed to develop and evaluate a WhatsApp-based application for reminding and monitoring IFAS intake using a Research and Development (R&D) approach with the Waterfall model. The development process included requirements analysis, system design, implementation, and testing, with data collected through interviews and observations at Sumber Primary Healthcare Center, Cirebon Regency, Indonesia. The application integrates automated WhatsApp reminders, daily IFAS consumption tracking, hemoglobin (Hb) data entry, and interactive graphical reporting features. Usability was assessed using the System Usability Scale (SUS) involving 30 adolescent girls. The application achieved an average SUS score of 66.3, indicating a Marginal level of acceptability with a Grade C rating. The results demonstrate that the system is functionally feasible as a tool to support the implementation and monitoring of IFAS supplementation programs. Nevertheless, further refinement is needed to improve user experience, interaction quality, and overall usability, thereby enhancing user acceptance and the effectiveness of digital health interventions among adolescent girls.